Voiced Postmemories: Rozalén’s “Justo” as a Case Study of Singing, Performing, and Embodying Mourning in Spain - Romera-Figueroa, Elia (Status Quaestionis, 2020)
This article introduces the concept of “voiced postmemories” by analyzing the song “Justo” (2017), created by the Spanish singer-songwriter Rozalén, as well as the documentary that was released with it, Conversaciones con mi abuela (2017). The documentary portrays an intergenerational dialogue in which Rozalén asks her grandmother about the murder and “disappearance” of Rozalén’s great-uncle, Justo, at the end of the Spanish Civil War. Justo’s story stands as an archetype of many stories of victims of authoritarian dictatorships. The song shows the need to mourn Justo for four generations. Among the achievements of Rozalén’s project is the exhumation of Justo’s tomb, reactivating an ongoing debate about mass graves in Spain. The essay connects this example with others in Spain, Chile, Uruguay, Israel, and India, and it characterizes some features of voiced postmemories, those aural and oral particularities of postmemories found and expressed through music and sound.